Effect of Sleep Disturbances on Blood Pressure - Makarem, Nour; Alcántara, Carmela; Williams, Natasha; Bello, Natalie A; Abdalla, Marwah (Hypertension (Dallas, Tex. 1979), 2021)
This review summarizes recent literature addressing the association of short sleep duration, shift work, and obstructive sleep apnea with hypertension risk, blood pressure (BP) levels, and 24-hour ambulatory BP. Observational studies demonstrate that subjectively assessed short sleep increases hypertension risk, though conflicting results are observed in studies of objectively assessed short sleep. Intervention studies demonstrate that mild and severe sleep restriction are associated with higher BP. Rotating and night shift work are associated with hypertension as shift work may exacerbate the detrimental impact of short sleep on BP. Further, studies demonstrate that shift work may increase nighttime BP and reduce BP control in patients with hypertension. Finally, moderate to severe obstructive sleep apnea is associated with hypertension, particularly resistant hypertension. Obstructive sleep apnea is also associated with abnormal 24-hour ambulatory BP profiles, including higher daytime and nighttime BP, nondipping BP, and a higher morning surge. Continuous positive airway pressure treatment may lower BP and improve BP dipping. In conclusion, efforts should be made to educate patients and health care providers about the importance of identifying and treating sleep disturbances for hypertension prevention and management. Empirically supported sleep health interventions represent a critical next step to advance this research area and establish causality.